Modeling and control of processes using the EMSO simulator and SIMATIC PLC as OPC inter-face (2018)
ABSTRACT : This work shows a procedure for modeling and control of level and flow processes. It uses the EMSO simulator to connect to a process by means of a SIMATIC S7-200 PLC as interface for the communication between the process instrumentation and the controller computing system. In order to supervise the variables, a SIMULINK model was connected to a laboratory process module through OPC communication. The model obtained was used in the design of controllers PID and PBSM, which were tested for step disturbances of the set point and an imposed set point trajectory.